Formation and evolution of residential buildings in the Djelfa region of Algeria - Salah Eddine Heffaf; Siham Bestandji; Nadjla Samah Hamida (Architecture Papers of the Faculty of Architecture and Design STU)
This study endeavours to refund the evolutionary trajectory of residential building within the Djelfa region of Algeria, a landscape characterised by the cohabitation of sedentary and nomadic modes of existence. The investigation reconstructs the typological development by examining its earliest roots, namely the rudimentary forms of habitation – the hut and the tent – respectively adapted to sedentary and nomadic lifestyles. A sample encompassing approximately sixty dwellings situated within the town of Djelfa and its environs was meticulously selected, ensuring representation of diverse typological features such as size, spatial arrangement within the urban fabric, orientation, accessibility, and internal spatial organisation. This analysis aims to discern both diachronic and synchronic variations: the enduring linkages between residential building types across time and the co-existence of concurrent typologies. The research reveals a dynamic of organic links of continuity throughout this evolutionary process, punctuated by transitional phases that give rise to novel building solutions. These innovative solutions, upon achieving a degree of stability, tend to be replicated in a serialized way. The study underscores the pivotal role of the urban courtyard house within this evolutionary narrative, emphasising its remarkable adaptability and capacity for diversification. This adaptability stems from its ability to evolve in response to varying initial layout conditions, driven by principles of iso-orientation and the direction of access within the enclosed space. The courtyard house serves as a foundational substratum for subsequent residential types, including the row house and the apartment building. The succession of residential typologies exhibits a cyclical oscillation, characterised by periods of expansion wherein the residential building expands through modular replication of the elementary cell, followed by periods of contraction and urban densification, leading to a reduction in unit size through subdivision of the plot.